ANALISIS KEPRIBADIAN EKSTROVERT TOKOH AVE DALAM NOVEL AGAVE KARYA MALASHANTI (KAJIAN PSIKOLOGI SASTRA) - Revina Rizki Alhudani; Haerussaleh Haerussaleh; Nuril Huda (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the extrovert personality of the character Ave in the novel Agave by Malashanti. The focus of this research is the extrovert personality type of the main character, Ave in the novel Agave by Malashanti. This research method is a type of qualitative descriptive research with a literary psychology approach. The data in this study is the dialogue of the main character, Ave, in the form of sentences, while the data source is the novel Agave by Malashanti. This novel Agave tells of a journalist named Ave who tries to interview the Director of a Hospital to achieve his dream of becoming a News Anchor in accordance with an agreement with her Supervisor. The results of this study indicate a conclusion that the extrovert personality type of Ave's character in the novel Agave by Malashanti is an extrovert thinker, extrovert feeling, extrovert sensing, and extrovert intuitive.